PARIWISATA CURUG BADAK DAN PENGARUHNYA PADA MASYARAKAT 2016-2021 - Fahmi, Ami Abdullah; Istiqomah, Durotun (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2021)
This research was conducted in a tourist spot that is quite crowded and visited by both teenagers and parents, namely the Curug Badak tour located in Tasikmalaya Regency. The aim of this research is to introduces natural tourism which is quite crowded in Tasikmalaya which is where this tour is a very beautiful natural tourism filled with the pine trees and the roar of the waterfall. Method used the author, namely the historical method through the collection of sources, both oral sources as well as in writing, in the source of the author's writing using a book that can be assist the author's research. The author conducted field observations to tourist attractions, interviews with the parties concerned to obtaining the required resources, and observing the books needed in the online library. The results of the author's research get is the fact that this Rhino Curug tour has been open for a long time and was inaugurated in 2016 since then it has had a positive impact on the surrounding communities, especially in the local economy. This matter proven when the author interviewed the people around him area, and when the author made direct observations to the place tour. The surrounding community also contributes a lot to the management Curug Badak tourism, this will certainly help tourism be more managed Besides that, the surrounding community also gets a lot of benefits from tourism nature that many fans.